The Impact of TikTok Social Media on Children's Language Politeness - Anggraeni, Sri Wulan; Robandi, Babang; Rahman (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
TikTok has become popular among children and teenagers, but there are concerns over the use of inappropriate and disrespectful language on the platform. This research aims to explore the impact of using the TikTok application on children's level of language politeness and the efforts made by parents to instill language politeness in children. This research uses a qualitative approach with a case study type. The research sample consisted of children aged 6-12 years. Data was collected through interviews and questionnaires. Data was analyzed using an interactive model, which consists of three elements, namely data reduction, data presentation, and concluding/verification. The research results show that the use of TikTok has a potential impact on children's language politeness. As many as 84% of respondents have encountered impolite content on TikTok, but the majority of children (89.5%) still use polite language when commenting. In addition, around 52.6% of respondents thought that the language on TikTok did not influence everyday language. These findings show that children, despite being exposed to impolite content, are still able to maintain polite language when interacting on TikTok, and the impact on their daily language is relatively minimal. In conclusion, TikTok has the potential to influence children's language politeness, and the role of parents in supervising and educating children on this platform is very important.